POLA DAN ETOS KERJA PEREMPUAN DALAM INDUSTRI RUMAH TANGGA DI JORONG CANGKIANG NAGARI BATU TABA KECAMATAN AMPEK ANGKEK KABUPATEN AGAM - Marleni Marleni (Universitas Islam Negeri Imam Bonjol Padang, 2013)
This article describes the role of women in domestic and public sphere. Multi-role women are able to maintain harmonious relations in their extended and core families. The main reason women have trading activities because of economic pressures. They feel they have a responsibility for their family livelihood sustainability. The interesting thing is they aware that their contributions to supplement their family income does not necessarily revoke roles as wife and mother in their family.Thus the women's role to implement various strategies in order to run smoothly, both in domestic and public aspects.Keywords : Women, have trading, domestic and public activityCopyright © 2013 by Kafa`ah All right reservedDOI : 10.15548/jk.v3i1.70